Thromboembolie in die Arterie eines Nierentransplantats durch Vorhofflimmern - Müller-Deile, Janina; Schwarz, A.; Menne, J. (Nieren- und Hochdruckkrankheiten, 2014)
Background: Central and peripheral arterial thromboembolisms are well known complications of atrial fibrillation. We report the first case of thromboembolism in a renal transplant due to atrial fibrillation after changing anticoagulation treatment. Case presentation: A 79-year-old woman who had undergone kidney transplantation in 2001 had a stable serum of 130-150 μmol/L since transplantation. Because of atrial fibrillation, the patient received oral anticoagulation treatment with Marcumar for many years until it was switched to aspirin (100 mg/d) due to a cholecystectomy in 2012. Three weeks thereafter is when the patient was admitted to our unit with abdominal pain and oliguria. In a computed tomography scan of the abdomen, multiple renal infarcts were detected. The thromboembolism resulted in a complete loss of transplant function. As the patient remained anuric, the transplant was declared to be lost, immunosuppression was reduced, and renal replacement therapy was commenced over a central catheter. However, the patient died the next day. Conclusion: Our case highlights the fact that changing anticoagulation treatment should be performed carefully and can be detrimental. The location of thromboembolism in renal transplant artery makes this case unique and has not ever been described thus far. As renal transplantation and risk factors for thromboembolism i.e., atrial fibrillation are increasing, embolization in renal transplant artery is a potential reason for abdominal pain and anuria; physicians should take this into consideration when treating transplanted patients. © 2014 Dustri-Verlag Dr. Karl Feistle.
CRIS-Team Scopus Importer:2020-11-12
Keywords: Atrial fibrillation; Kidney transplantation; Thromboembolization